Is an interatrial communication the same as an atrial septal defect? - Robert H Anderson (University of São Paulo, 2011)
It is, perhaps, unfortunate that those using Anglo-saxon tongues, as opposed to romantic languages such as French, Spanish, Italian, or Portuguese, should describe holes permitting shunting between the atrial chambers as septal defects rather than interatrial communications. This is because, of necessity, the understanding of deficiencies of the atrial septum is entirely dependent on the definition of the structures considered to represent the atrial septum.